2021
DOI: 10.3390/nu13113921
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Nootkatone on Renal Inflammation, Apoptosis, and Fibrosis in a Unilateral Ureteral Obstructive Mouse Model

Abstract: Nootkatone is one of the major active ingredients of Alpiniae oxyphyllae, which has been used as both food and medicinal plants for the treatment of diarrhea, ulceration, and enuresis. In this study, we aimed to investigate whether nootkatone treatment ameliorated the progression of chronic kidney diseases (CKD) and clarified its underlying mechanisms in an obstructive nephropathy (unilateral ureteral obstructive; UUO) mouse model. Our results revealed that nootkatone treatment preventively decreased the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…NK is also isolated from grapefruit and pummel [13]. It has been reported that NK has several pharmacological properties such as antimicrobial, antioxidant, antifibrotic and anti-allergic activities [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NK is also isolated from grapefruit and pummel [13]. It has been reported that NK has several pharmacological properties such as antimicrobial, antioxidant, antifibrotic and anti-allergic activities [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Since cardiac toxicity related to DOXO involves oxidative stress and apoptosis at early events and fibrosis and cardiac dysfunction as late events and NK has potential anti-oxidant activities at early events as well as has palliative effects against some experimental diseases involving inflammation and oxidative stress [6,10,[14][15][16][17][18][19][20], we considered that it was relevant to assess the possible protective effects of NK on early DOXO-induced cardiac toxicity and the mechanisms underlying these effects in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Nahuoic acid A (29), oleamide (37), erucamide (52), oligomycin C (78), and plakevulin A (101) are known as inhibitors of different enzymes [52][53][54][55]. Some of identified compounds (17,18,34,37,41,59, and 111) are characterized by anti-inflammatory or antimalarial properties [42,43,49,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis (a programmed cell death) of glomerular ECs, podocytes, and TECs is closely associated with RF (Thomas et al, 1998;Docherty et al, 2006). Inhibition of apoptosis as a therapeutic target can alleviate fibrosis (Chen et al, 2021;Xia et al, 2021;Park et al, 2022). Cordyceps downregulates apoptosis in ischemia/reperfusion injury and Cyclosporine A-induced renal tubular dysfunction (Shahed et al, 2001;Chyau et al, 2014).…”
Section: Cordyceps Inhibits Apoptosismentioning
confidence: 99%